2015
DOI: 10.1002/chem.201502335
|View full text |Cite
|
Sign up to set email alerts
|

Chirality‐ and pH‐Controlled Supramolecular Isomerism in Cobalt Phosphonates and Its Impact on the Magnetic Behavior

Abstract: Two pairs of enantiomeric compounds with formulas (S)- or (R)-Co3 (ppap)2 (4,4'-bpy)2 (H2 O)2 ⋅4 H2 O [(S)-1 or (R)-1], (S)- or (R)-Co3 (ppap)2 (4,4'-bpy)2 (H2 O)2 ⋅3 H2 O [(S)- or (R)-2), and related racemic compound Co3 (ppap)2 (4,4'-bpy)2 (H2 O)2 ⋅4 H2 O (rac-3; 4,4'-bpy=4,4'-bipyridine, H3 ppap=3-phenyl-2-[(phosphonomethyl)amino]propanoic acid) are reported. Compounds 1 and rac-3 show identical three-dimensional framework structures, whereas compounds 2 have two-dimensional layer structures. Compounds 1 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…The magnetic susceptibility χ M and χ M T versus T of 1 were measured at a constant magnetic field of 1000 Oe in the range of 1.8–300 K, as shown in Figure . The χ M value of 1 was 0.04 emu mol –1 at 300 K; with cooling of the temperature, the χ M value of 1 quickly increased to a maximum value of 4.46 emu mol –1 at 1.8 K. The value of χ M T at 300 K is 11.84 emu K mol –1 , which is much higher than the theoretical value of 5.63 emu K mol –1 for three noninteracting high-spin Co II ions calculated from the Van Vleck equation ( S = 3 / 2 , g = 2) . As the temperature decreases, the value of χ M T reduced to a minimum of 8.64 emu K mol –1 at 25 K. Afterward, the χ M T value increased rapidly to reach a maximum of 9.39 emu mol –1 K at about 4 K and then lessened sharply to 8.91 emu mol –1 K at 1.8 K. The decrease in the 300–25 K temperature range is attributed to spin–orbit coupling of Co II , while the maximum at 4 K is indicative of the ferromagnetic Co II –Co II interactions within the trinuclear spin cluster .…”
Section: Resultsmentioning
confidence: 65%
“…The magnetic susceptibility χ M and χ M T versus T of 1 were measured at a constant magnetic field of 1000 Oe in the range of 1.8–300 K, as shown in Figure . The χ M value of 1 was 0.04 emu mol –1 at 300 K; with cooling of the temperature, the χ M value of 1 quickly increased to a maximum value of 4.46 emu mol –1 at 1.8 K. The value of χ M T at 300 K is 11.84 emu K mol –1 , which is much higher than the theoretical value of 5.63 emu K mol –1 for three noninteracting high-spin Co II ions calculated from the Van Vleck equation ( S = 3 / 2 , g = 2) . As the temperature decreases, the value of χ M T reduced to a minimum of 8.64 emu K mol –1 at 25 K. Afterward, the χ M T value increased rapidly to reach a maximum of 9.39 emu mol –1 K at about 4 K and then lessened sharply to 8.91 emu mol –1 K at 1.8 K. The decrease in the 300–25 K temperature range is attributed to spin–orbit coupling of Co II , while the maximum at 4 K is indicative of the ferromagnetic Co II –Co II interactions within the trinuclear spin cluster .…”
Section: Resultsmentioning
confidence: 65%
“…The χ M T value at room temperature (300 K) of 9.74 emu K mol −1 is much higher than the expected value of 5.63 emu K mol −1 for three spin-only Co II ions (S = 3 / 2 and g = 2), which is associated with the strong orbital contribution of the high-spin octahedral Co 2+ . 24 The χ M T versus T curve exhibits a continuous decrease smoothly from 300 K to a minimum of 7.57 emu K mol −1 at 18 K. Below 18 K, the χ M T value increases rapidly to reach a maximum of 7.96 emu K mol −1 at about 5 K and then falls sharply to 7.59 emu K mol −1 at 1.8 K. The decrease of χ M T from room temperature is due to the characteristic spin−orbit coupling of the single Co II ions, while the sharp upturn of χ M T at the low temperature is indicative of the ferromagnetic Co•••Co interactions within the trinuclear spin cluster. Finally, the χ M T value decreases below 5 K, which is related to magnetic anisotropy.…”
mentioning
confidence: 99%
“…Supramolecular isomers which have an identical chemical composition but different network structures or morphologies have received increasing attention in the molecular and crystal engineering areas. A number of studies on the supramolecular isomerism have been reported so far, and the factors such as temperature, solvent, template, pH, , catenation, molar ratio, , and concentration have been found to affect the formations of particular supramolecular isomers. However, it is still important to find and understand the factors that induce the formation of supramolecular isomers.…”
Section: Introductionmentioning
confidence: 99%